ANALISIS KANDUNGAN AKRILAMIDA DALAM UBI GORENG YANG DIJUAL DI KOTA MANADO MENGGUNAKAN KROMATOGRAFI CAIR KINERJA TINGGI (KCKT) - Sengke, Clara A.; Citraningtyas, Gayatri; Wehantouw, Frenly (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACTAcrylamide is caused by a high temperature (more than 1200C) in the food that contains highcarbohydrate. Acrylamide was classified as senyawa that caused cancer or have highpotention as carcinogenic compound in the human body. Junk food which mostly eaten bypeople is fries. The aims of this research were to identify how much acrylamide was containsin sweet potato fries that has been sell at Manado City using High Performance LiquidChromatography (HPLC) method. The samples that has been identified is came from 7 storein 7 sub district at Manado City. In this research, the acrylamide were analysed with HighPerformance Liquid Chromatography using Shim-Pack VP-ODS (4,6 x 250 mm) column,comparison of mobile phase acetonitrile and phosphate acid 11,45 mM (20 : 80), flow rate 1ml/minute and at wave length 210 nm. The result shows acrylamide found in sweet potatofries with retention time Â±3,311 minutes. Acrylamide that contains in sweet potato frieswhich has been sell in Manado City were 118,54-866,75 Î¼g/kg. Acrylamide level that foundin sweet potato fries is still under lethal dose.Keywords : Acrylamide, sweet potato fries, HPLC, Manado